Orthorhombic charge density wave on the tetragonal lattice of EuAl4. (2022) - Ramakrishnan, Sitaram; Kotla, Surya Rohith; Rekis, Toms; Bao, Jin-Ke; Eisele, Claudio; Noohinejad, Leila; Tolkiehn, Martin; Paulmann, Carsten; Singh, Birender; Verma, Rahul; Bag, Biplab; Kulkarni, Ruta; et al.
No abstract available